PERAN HUKUM DALAM PENYELENGGARAAN SISTEM TRANSPORTASI DARAT - BELAWAN, ANGGA PUTRA (Dinamika Hukum, 2017)
Land transportation system is a unity of activities and management in support of every activity moving the human place continuously without knowing the boundaries of the region and time. The vital role of the transport system needs to be supported by the general public, business and government. In this case, the state is obliged to guarantee the implementation of the land transportation system properly and sustainably. This study aims to determine the current condition of Land Transportation System and provide input / suggestions on UU No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan and UU No.23 Tahun 2014 tentang Pemerintahan Daerah. Research on the Role of Law in the Implementation of Land Transportation System is a normative legal research. In this study to examine the systematic law of the conflict of norms that exist in the Undang- Undang Dasar 1945, UU No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan and UU No. 23 Tahun 2014 tentang Pemerintahan Daerah, viewed from the Legal philosophy, legal theory, state science and transportation rules. Based on the research, it is found that there are many articles of contradiction in UU No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan and UU No. 23 Tahun 2014 tentang Pemerintahan Daerah, especially in the regulation of land transportation system. The contradiction of the norms takes place both in the same law as well as in different laws but governing the same. Therefore, the preparation of legal products in relation to the Land Transportation System should further bring the spirit that accommodates that the Transport System is a series of borderless / can not restricted transportation activities. Then combined with the spirit of the Good and Clean Governance program in the service of public transportation needs by agreeing that transportation is the backbone of the State in almost all areas so it is a vital subsystem in realizing the ideals of the State. Arrangement of the future land transportation system should be directed as the interests of the State so it can easily be arranged to be simultaneous and integrated with the sea and air transportation system. So the legal consequence is the authority of arranging the transportation system is drawn to the Central Government while the Regional Government as a supporter in conducting supervision and control of transportation activities. Keywords: Role of Law, Land Transportation System